Kinetics of Oxidation Inhibition of Sodium Sulphite in Wet Flue Gas Desulphurization Process - Guo, Shaopeng; Chen, Xin; Tong, Ming; Shen, Zhigang; Zhou, Yanbo; Zhang, Rui; Lu, Jun (Asian Journal of Chemistry, 2013)
The effect of several inhibitors on the oxidation rate of sodium sulphite was determined by both intrinsic and macroscopic experiments using self-designed bath reactor. The results indicated that ethanol is the most suitable inhibitor for wet flue gas desulphurization due to its low cost and non-toxicity. The oxidation kinetics of sodium sulphite inhibited by ethanol was studied using stirred bubbling reactor by varying concentration of sodium sulphite and ethanol, air flow rate and temperature. The reaction orders of all regents and the apparent activation energy of the reaction were achieved. Finally, a kinetic model was established based on the experimental results, which would be useful for the process optimization of the wet flue gas desulfurization systems.